Synergistic Effect of Quercetin and α-Lipoic Acid on Aluminium Chloride Induced Neurotoxicity in Rats - Sooad Saud Al-Otaibi; Maha Mohamad Arafah; Bechan Sharma; Abdullah Salih Alhomida; Nikhat Jamal Siddiqi (Journal of Toxicology)
Objectives. The present study was carried out to study the protective effects of quercetin and α-lipoic acid alone and in combination against aluminum chloride induced neurotoxicity in rats. Materials and Methods. The study consisted of eight groups, namely, Group 1: control rats, Group 2: rats receiving aluminium chloride 7 mg/kg body weight intraperitoneal route (i.p) for two weeks, Group 3: rats receiving quercetin 50 mg/kg body weight i.p. for two weeks, Group 4: rats receiving quercetin 50 mg/kg body weight followed by aluminium chloride 7 mg/kg body weight i.p. for two weeks, Group 5: rats receiving α-lipoic acid 20 mg/kg body weight i.p. for two weeks, Group 6: rats receiving lipoic acid 20 mg/kg body weight followed by aluminium chloride 7 mg/kg body weight i.p. for two weeks, Group 7: rats receiving α-lipoic acid 20 mg/kg body weight and quercetin 50 mg/kg body weight i.p. for two weeks, and Group 8: rats receiving α-lipoic acid 20 mg/kg body weight and quercetin 50 mg/kg body weight followed by aluminium chloride 7 mg/kg body weight i.p. for two weeks. The animals were killed after 24 hours of the last dose by cervical dislocation. Results. Aluminium chloride treatment of rats resulted in significant increases in lipid peroxidation, protein carbonyl levels, and acetylcholine esterase activity in the brain. This was accompanied with significant decreases in reduced glutathione, activities of the glutathione reductase, and superoxide dismutase. Pretreatment of AlCl3 exposed rats to either quercetin or α-lipoic acid also restored altered lipid peroxidation and superoxide dismutase to near normal levels. Quercetin or α-lipoic acid pretreatment of AlCl3 exposed rats improved the protein carbonyl and reduced glutathione, glutathione reductase, and acetylcholine esterase activities in rat brains towards normal levels. Combined pretreatment of AlCl3 exposed rats with quercetin and α-lipoic acid resulted in a tendency towards normalization of most of the parameters. Conclusions. Quercetin and α-lipoic acid complemented each other in protecting the rat brain against oxidative stress induced by aluminium chloride.